Two years of clinical experience with norethisterone enanthate injectable contraceptive depot. - Larrañaga, Alfredo (2015)
Treatment of 1036 patients from rural (29.7 %) and urban (70.3 %) origin with norethisterone enanthate, a long term progestogen used as a contraceptive, is reported. The contraceptive effect is high, failure rate being 1.58 per 100 woman-years. Protection is extended far 12 weeks and the effect is reversible. Disturbances were present in 35.4% of the cycles, specially when treatment was started in postpartum amenorrheic, lactating women. The most frequent alteration was poli-hypermenorrhea. Intermenstrual spotting or bleeding tends to decrease after the initial months of treatment. The low incidence in inhibition of lactation as well as in general side effects, and its marked acceptability among women of low social-economic level are highly positive facts far this new contraceptive measure.